2020
DOI: 10.1089/cyber.2019.0545
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Leading to Preference for Extreme Facial Retouching

Abstract: Young women posting their edited face photographs on social networking sites have become a popular phenomenon, but an excessively retouched face image sometimes gives a strange impression to its viewers. This study investigates what personal characteristics facilitate a bias toward an excessively edited face image. Thirty young Asian women evaluated the attractiveness and naturalness of their face images, which were edited in eight different levels-from mild to excessive-by expanding their eyes and thinning th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
3
5
0
Order By: Relevance
“…A previous study, which manipulated facial attractiveness by contrast effect, also reported that medial cortical regions and the VTA, the center of human dopaminergic reward system, exhibit greater activation when self-face looks more attractive than other-face (Oikawa et al, 2012). Consistently, our previous behavioral study has shown that young women prefer stronger beauty filters on their own face than on others' faces (Nakano & Uesugi, 2020). This suggests that the enhanced attractiveness of self-face has a higher reward value than that for otherface and that, as a result, the preference for using beauty filters on their own face is reinforced.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…A previous study, which manipulated facial attractiveness by contrast effect, also reported that medial cortical regions and the VTA, the center of human dopaminergic reward system, exhibit greater activation when self-face looks more attractive than other-face (Oikawa et al, 2012). Consistently, our previous behavioral study has shown that young women prefer stronger beauty filters on their own face than on others' faces (Nakano & Uesugi, 2020). This suggests that the enhanced attractiveness of self-face has a higher reward value than that for otherface and that, as a result, the preference for using beauty filters on their own face is reinforced.…”
Section: Introductionsupporting
confidence: 85%
“…As described above, since positive modulation by beauty retouching activates the reward system, facial retouching behaviors using beauty filter app become reinforced. In fact, young women prefer to apply stronger beauty filters on their own face than on others' faces (Nakano & Uesugi, 2020). Conversely, the amygdala induces negative reactions towards excessively retouched faces, which helps suppress the reinforced behavior of retouching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study, which manipulated facial attractiveness by contrast effect, also reported that medial cortical regions and the VTA, the center of human dopaminergic reward system, exhibit greater activation when self-face looks more attractive than other-face (Oikawa et al, 2012). Consistently, our previous behavioral study has shown that young women prefer stronger beauty filters on their own face than on others' faces (Nakano & Uesugi, 2020). This suggests that the enhanced attractiveness of self-face has a higher reward value than that for other-face and that, as a result, the preference for using beauty filters on their own face is reinforced.…”
Section: Introductionsupporting
confidence: 80%
“…Moderate beauty retouching can increase facial attractiveness, but in cases of excessive use, it can make a face appear unnatural and even creepy. Ironically, the facial attractiveness then becomes much lower than that of the original face (Nakano & Uesugi, 2020). Since extreme facial retouching creates a face whose balance between individual parts and overall structure deviates from the distribution of real humans (e.g., extremely big eyes and very thin chins), the negative impression toward the extremely retouched faces may be related to the "uncanny valley" phenomenon, in which eerie sensations are induced when viewing subjects with slight differences that cause them to look like false or unreal humans (Feng et al, 2018;Mori et al, 2012).…”
Section: Introductionmentioning
confidence: 99%